The Role of Clinical Pharmacy in Preventing Complications of Metabolic Syndrome - Annis Rahmawaty (Pt. Anagata Sembagi Education, 2025)
Metabolic syndrome is a cluster of interacting metabolic risk factors, including central obesity, hypertension, insulin resistance, hyperglycemia, and atherogenic dyslipidemia, which significantly increase the risk of cardiovascular disease and type 2 diabetes mellitus. The prevalence of metabolic syndrome continues to increase globally due to changes in sedentary lifestyles and high-calorie consumption patterns, making it a public health issue with serious clinical, social, and economic impacts. The resulting complications, such as coronary heart disease, stroke, chronic kidney failure, and neuropathy, not only worsen patients' quality of life but also increase long-term healthcare costs. Therefore, preventing complications needs to be prioritized with strategies that integrate healthy lifestyle modifications, medical interventions, and rational pharmacotherapy. Clinical pharmacists play a strategic role in the management of metabolic syndrome through medication therapy management (MTM), patient education, drug interaction detection, and increased therapy adherence. Interdisciplinary collaboration between pharmacists, physicians, nurses, nutritionists, and psychologists strengthens the effectiveness of comprehensive, more personalized interventions. This study uses qualitative methods through a literature review to analyze the role of clinical pharmacists in preventing metabolic syndrome complications. The results show that integrating the role of clinical pharmacists into the healthcare team, supported by regulations, technology, and ongoing training, is key to reducing the risk of complications and improving people's quality of life.